Numerical study of structure-subsoil interactions under seismic effects - Bazhenov, Valentin Georgievich; Dyukina, Nadezhda Sergeevna (Computational Continuum Mechanics, 2012)
A mathematical model and a numerical method for analyzing problems of the dynamics of structures under seismic vibrations are presented. The proposed approach takes into account the interaction between the structure and the subsoil. When representing the half-space as a finite rectangular computational domain, special boundary conditions that do not distort incident seismic waves are introduced. Kinematic boundary conditions at the lower boundary of the computational domain are determined from the experimental accelerograms recorded at the surface of the half-space. The seismic vibrations of structures have been studied with allowance for their contact interaction with soil foundations at different parameters: solidity, eccentricity of the mass centre of the structure, depth of the underground part of the foundation, friction at the contact surface, seismic load intensity, and multilayered nature of the soil basis.
Keywords: seismic loading; mathematical model; numerical modeling; contact interaction; structure/subsoil interaction